Penerapan Exergames Berbasis Android sebagai Neurorehabilitasi pada Pasien Pasca Stroke - Elya Sespa; Tuti Herawati; Denissa Faradita Aryani (Journal of Telenursing (JOTING), 2023)
This study aims to provide an overview and ideas from the results of a literature review regarding the possibility of implementing neurorehabilitation in post-stroke patients with the android-based exergames method. The method used is a literature review of databases: Scopus, ScienceDirect, ProQuest, Sage Journal, Ebscohost, Sage Publication, Google Scholar, and Semantic Scholar from 2018-2022. The research results show the results of a review of 10 selected journals; exergames are a very flexible tool for neurorehabilitation in post-stroke patients suffering from various neurological disorders. In conclusion, the application of exergames as an android-based neurorehabilitation as an effective method can be carried out in post-stroke patients. Keywords: Android, Exergames, Neurorehabilitation, Post Stroke